Gene aberrations and methylation analysis of JAK/stat and toll-like receptor downstream signalling in BCR-ABL-negative myeloproliferative neoplasms and myelodysplastic syndrome/myeloproliferative neoplasms overlap syndromes - Cai, Chia Yuh (2021)
BCR-ABL-negative myeloproliferative neoplasms (MPN) and myelodysplastic syndrome/myeloproliferative neoplasms (MDS/MPN) overlap syndromes are myeloid malignancies result from genetics, epigenetics and chromosomal mutational events, particularly in janus kinase/signal transducers and activators of transcription (JAK/STAT) and toll-like receptor (TLR) signalling pathway. This study was to estimate the prevalence, identify the mutational status of JAK2, TET2 and MyD88 genes, and methylation status of SOCS3 and INPP5D genes in these diseases. TET2 gene mutations in BCR-ABL-negative MPN was selected for a meta-analysis. The same archived DNA samples were used for mutational and methylation analysis. The mutational status of JAK2, TET2 and MyD88 genes in BCR-ABL-negative MPN and MDS/MPN were studied through direct sequencing. The methylation status of the promoter region for SOCS3 and INPP5D genes were studied using pyrosequencing. For exon 26 of the INPP5D gene was analysed using methylation-specific PCR. Normal controls were included. It was estimated that the overall pooled prevalence of TET2 gene mutations in BCR-ABL-negative MPN was 15.5%. JAK2 V617F, five missense variants (M532I, M535R, V536G, R541K and D544N), one novel intronic single nucleotide polymorphisms (SNP) (c.1194+12G>A) and two novel deletions (c.1157delT and c.1160delT) in JAK2 exon 12 and an intronic SNP in MyD88 (rs4988457) were detected. JAK2 V617F was frequently found in BCR-ABL-negative MPN (85.4%) and MDS/MPN (50.0%). The missense variants in JAK2 exon 12 (27.1%) and MyD88 (7.3%) were detected in BCR-ABL-negative MPN only. The methylation level of SOCS3 promoter, INPP5D promoter and INPP5D exon 26 showed no significant difference with normal controls. TET2 gene mutations could contribute to the initiation and development of BCR-ABL-negative MPN. The mutations were also believed to be related to thrombosis, leukaemic transformation and had a close relationship with other gene mutations found in the disease. However, more studies were needed. JAK2 V617F was highly associated with BCR-ABLnegative MPN and MDS/MPN. Mutations in JAK2 exon 12 seemed to be specific to BCR-ABL-negative MPN and were suggested to be studied in granulocytes since the mutations were found in granulocytes. A study on the expression of the MyD88 gene with rs4988457 in blood malignancies is recommended in the future. The methylation status of the SOCS3 promoter near the transcription start site can also be analysed in BCR-ABL-negative MPN.